School as Learning Communities: An Effective Alternative for Adult Education and Literacy in Brazil - Mello, Roseli Rodrigues; Braga, Fabiana Marini (Frontiers in Education, 2018)
Women and men, young and adult, who have reached youth or adult life without elementary schooling are part of an important and vulnerable group in Latin America, as for instance Brazil. Integrating the studies that seek to contribute to a qualitative change in Brazilian Adult Education, as a means for overcoming inequalities and in support of most vulnerable groups within the population, this article regards the case of the first Adult Education School in Brazil to transform the learning community. The research was developed between 2014 and 2016 and refers to a qualitative case study using the communicative approach, guaranteed by the use of the Communicative Methodology. Data was collected using four techniques pertaining to the Communicative Methodology: communicative in-depth interview with the school’s Adult Learning and Education coordination; communicative daily-life story with students and volunteers; communicative focus groups with students, volunteers and teachers; and communicative observation in Successful Educational Actions. The results indicate transformative and excluding elements that emerged in the following categories: the school’s characteristics studied, work and life conditions and access to schooling and continuity in school, and interaction within the learning community. Comparing the results that indicate positive aspects of the Adult Learning and Education school transformed into learning communities to results in other studies about other successful Adult Learning and Education schools in Brazil, it can be established that they coincide in some aspects and go beyond others. Although coincidence between studies was observed, they were more intensely noticed in the learning community regarding the following aspects: a) school management oriented towards learning, with contact mechanisms with students that began missing classes, b) appreciation, from the school staff, of teaching and learning processes, specially reading and writing, c) a welcoming environment, bonding between professionals and students, and high expectations towards students. As for the elements identified in the learning community which were not found in the other Brazilian studies, they were: a) enrollment increase over time and decrease in student dropout rates throughout the year, and b) overcoming dramatic situations experienced in the neighborhood and in the school that could initially lead to school dropout.